A Hindu perspective to organizational learning. Issue 6 (11th September 2017) - Shama Rao, Ashok; Kamath Burde, Jyothsna
Abstract : Purpose: This paper aims to provide an overview of the relevance and applicability of the Hindu tradition to organizational learning. Design/methodology/approach: Attempting to separate the spiritual from the religious aspects, a primarily theoretical approach is used to delineate the basic concepts in Hinduism and their applicability to various aspects of employee and organizational functioning. Findings: Concepts such as Yoga, Dharma, Karma, Yajna and Lokasamgraha are discussed. Originality/value: This paper stems from the recognition of cultural differences and the need to explore alternative paradigms to understand and enhance organizational functioning.